(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2026)
This article discusses the role, significance and effectiveness factors of legal education in preventing offenses committed by students in secondary schools. The content and methods of the legal education system, the role of school, family and community cooperation in the prevention of offenses are scientifically analyzed. It also suggests ways to reduce the factors that contribute to the occurrence of offences by forming a legal awareness and culture of pupils.